THE RISE OF NON-NATIVE ENGLISH ACCENTS - Karimjonovna Shakhlokhon Ravshanjonovna; Madaminova Durdonaxon Abduxakim qizi (TADQIQOTLAR, 2025)
Annotation.  This  article  explores  the  rise  of  non-native  English  accents, examining  the  key  factors  behind  their  growing  acceptance  and  prominence.  It highlights  the  role  of  globalization,  technological  innovation,  and  the  increasing diversification of media in shaping the spread of English across the world. Non-native English speakers are now more visible in global communication, with platforms such as social media, streaming services, and the widespread use of English in education and the workforce offering them an increasingly prominent stage. The  article  further  explores  how  the  traditional  perceptions  of  "correct" English—once dominated by native accents from countries like the UK and the US—are  being  challenged.  As  the  article  points  out,  accents  are  deeply  tied  to  cultural identity, and this growing acceptance of non-native accents reflects a shift towards embracing  linguistic  diversity.  In  academic  and  professional  spheres,  non-native accents are increasingly recognized as assets that contribute to global competency, cultural  understanding,  and  inclusivity,  rather  than  as  limitations.  This  evolution represents a broader trend towards recognizing the value of linguistic diversity in a globally interconnected world